Pengembangan Skala Kemandirian - Suharnan, * (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. One of the most problems that often faced by researchers is unavailable of instruments to measure variables. Therefore, the present research purposed to develop independent scale as one of some psychological measures which could be used to studies in the future. The independent scale was constructed according to psychometric prosedures and consists of the number of items composed of four components. This research was conducted in two studies, and including 331 subjects (male and female) of students coming from some high schools and a university. Statistical analyses were used to examine data of the scale. Results showed the constructed independent scale was reliable and valid to measuring independent behaviors of individuals.Â  Keywords: independent scale, measurement